Interactions between multi-walled carbon nanotubes and plankton as detected by Raman spectroscopy. (May 2022) - Howarth, Jack R.; White, Alvin Orbaek; Hedayati, Ali; Niu, Yubiao; Palmer, Richard E.; Tang, Kam W.
Abstract: Raman spectroscopy has been commonly used in materials science to detect chemicals. Based on inelastic scattering of light after incident photons interact with a molecule, it has high potential for non-destructive detection of specific contaminants in living biological specimens. The increasing use of carbon nanotubes (CNTs) increases its chance to enter the aquatic habitats through direct discharge, surface runoff and atmospheric deposition, but their potential environmental impacts remain poorly known. We tested the use of Raman spectroscopy to investigate the interactions between multi-walled CNTs (MWCNTs) and aquatic plankton in vivo . For phytoplankton cells ( Scenedesmus obliquus ) that were exposed to MWCNTs, Raman spectroscopy was able to distinguish between background biological material and MWCNTs that adhere to the cells (G-band peak at 1590 cm −1 and D-band peak at 1350 cm −1 in the Raman spectra that were unique to MWCNTs). Harmful effects of MWCNT exposure manifested as lower photosynthetic efficiency and/or lower specific growth rate in the phytoplankton. MWCNT particles also adhered to the body surface of zooplankton, especially the carapace. Both Ceriodaphnia sp. and Daphnia sp. ingested MWCNTs directly, which was verified by the signature G-band and D-band Raman peaks in the zooplankton gut region. MWCNTs remained in the gut overnight after the zooplankton had been returned to clean water, showing that the zooplankton retained MWCNTs inside their body for an extended time, thereby increasing the chance to disperse and transfer the contaminants throughout the aquatic food web. Our results demonstrate that Raman spectroscopy is a promising method for non-destructive investigation of the uptake and dynamic fate of CNTs and other contaminants in aquatic organisms. Graphical abstract: Image 1 Highlights: Raman spectroscopy was able to detect MWCNTs in biological specimens in vivo. Exposure to MWCNTs decreased phytoplankton photosynthetic efficiency and/or specific growth rate. Zooplankton could dislodge some of the externally attached MWCNTs by grooming. Zooplankton ingested and retained MWCNTs in their guts for an extended time.